Myocardial perfusion during atrial fibrillation in patients with non-ischaemic systolic heart failure: a cross-sectional study using Rubidium-82 positron emission tomography/computed tomography. (9th July 2018) - Byrne, Christina; Hasbak, Philip; Kjær, Andreas; Thune, Jens Jakob; Køber, Lars
Abstract: Aims: Patients with non-ischaemic systolic heart failure often have reduced myocardial blood flow without significant coronary atherosclerosis. Likewise, patients with atrial fibrillation (AF) have reduced myocardial perfusion during AF compared with sinus rhythm. The aim of this study was to explore whether there is an additive negative effect of AF during scan on the myocardial perfusion in patients with non-ischaemic systolic heart failure. Methods and results: We included 27 young healthy controls and 114 patients with non-ischaemic systolic heart failure to a Rubidium-82 positron emission tomography/computed tomography perfusion scan (23 with AF during scan). To obtain the myocardial flow reserve (MFR = stress flow/rest flow), patients were scanned at rest and during adenosine-induced stress. Among patients, those with AF were older [years: 73; interquartile range (IQR) 65–78 vs. 67; IQR 60–74; P = 0.03] and more were men (87% vs. 62%; P = 0.02). Distribution of sex in controls did not differ from either patient group. Patients with AF had significantly lower MFR than patients without [MFR: 1.87; 95% confidence interval (CI) 1.58–2.22 vs. 2.50; 95% CI 2.06–2.86; percent difference: −21.5%; P = 0.01]. MFR remained significantly lower in the group with AF (estimate −24.2%; 95% CI −39.6% to −4.8%; P = 0.02) in an adjusted multivariable regression analysis. Further, patients had lower MFR compared with controls: 3.46; 95% CI 3.03–3.94; P < 0.0001. Additionally, coronary vascular resistance was highest in patients with AF and lowest in controls. Conclusion: Patients with systolic heart failure had lower flow reserve than healthy controls and even lower MFR if they had AF during scan.